Distribution of dissolved inorganic carbon and related parameters in the Thermaikos Gulf (Eastern Mediterranean) - KRASAKOPOULOU, E.; ANAGNOSTOU, CH.; SOUVERMEZOGLOU, E.; PAPATHANASSIOU, E.; RAPSOMANIKIS, S. (Mediterranean Marine Science, 2006)
Data on the distribution of dissolved inorganic carbon (measured as TCO2) and related parameters in the Thermaikos Gulf were obtained during May 1997. High TCO2 concentrations were recorded close to the bottom, especially in the northern part of the gulf, as a result of organic matter remineralisation. The positive relatively good correlation between TCO2 and both apparent oxygen utilisation (AOU) and phosphate at the last sampling depth confi rmed the regenerative origin of a large proportion of TCO2. The comparatively conservative behaviour of alkalinity, together with the relatively low value of the homogenous buffer factor β (β = ∂lnfCO2/∂lnTCO2) revealed that calcifi cation or carbonate dissolution takes place on a very small scale, simultaneously with the organic carbon production. The correlations between fCO2 and chlorophyll α, as well as AOU and the surface temperature, revealed that the carbon dioxide fi xation through the biological activity is the principal factor that modulates the variability of fCO2. A rough first estimate of the magnitude of the air-sea CO2 exchange and the potential role of the Thermaikos Gulf in the transfer of atmospheric CO2 was also obtained. The results showed that during May 1997, the Thermaikos Gulf acted as a weak sink for atmospheric CO2 at a rate of -0.60 - -1.43 mmol m-2 d-1, depending on which formula for the gas transfer velocity was used, and in accordance to recent reports regarding other temperate continental shelves. Extensive study of the dissolved inorganic carbon and related parameters, and continuous shipboard measurements of fCO2 a and fCO2 w during all seasons are necessary to safely quantify the role of the Thermaikos Gulf in the context of the coastal margins CO2 dynamics.